STANDARDIZATION OF PERIOPERATIVE CARE IN ANAESTHESIOLOGY: ASSESSMENT OF THE SITUATION IN UKRAINE ACCORDING TO THE RESULTS OF SOCIOLOGICAL SURVEY AMONG DOCTORS - Федосюк, Р.М. (World of Medicine and Biology, 2016)
Over the past 10 years, the WHO and the leading international professional organizations of anaesthesiologists and intensive care specialists have introduced a number of important initiatives on patient safety in order to address the problem on a global scale. The level of implementation of these initiatives in the domestic service of anaesthesiology remains unknown. The sociological study that included 282 anaesthesiologists from the hospitals of Ukraine has been conducted. The questionnaire was designed to analyze the level of implementation of perioperative technological algorithms, clinical protocols, and standards of monitoring in Ukraine. Most anaesthesiologists (85.8% of respondents) reported the introduction of minimum perioperative monitoring standards at their institutions, and 77.3% of physicians responded positively to questions about the availability of the local protocol for the control of anaesthesiologist’s workplace readiness. About 70% of respondents reported the presence of algorithms and protocols of care in case of complications during anaesthesia at their institutions. Only 45.0% of physicians from medical institutions of the II level and 55.7% of physicians from institutions of the III-IV levels reported that all anaesthetic interventions at their establishments were conducted under constant monitoring of heart rate, blood pressure, and saturation. 8.5% of respondents reported the implementation of the «WHO Surgical Safety Checklist» or its adapted version at the structural units in the anaesthesiology service. The level of implementation of perioperative technological algorithms, clinical protocols, and standards for monitoring at the structural units in the anaesthesiology service of Ukraine is inadequate.
Keywords: anesthesiology; perioperative monitoring; check-lists; sociological study